ANALISIS KESULITAN PEMELAJAR BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DI SAMARKAND STATE INSTITUTE OF FOREIGN LANGUAGES (SAMSIFL), UZBEKISTAN PADA 4 KETERAMPILAN (SKILLS) BERBAHASA - NASUTION, JAMALUDDIN (Jurnal Ilmiah Aquinas, 2020)
This research entitles â€œThe Analysis of Difficulties of IndonesianÂ Â Language for Foreign Speakers (ILFS) Students in Samarkand State Institute of Foreign Languages, Uzbekistan toward 4 Language Skillsâ€. There are some language skills, i.e.; (1) listening skills), (2) speaking skills, (3) reading skills, and (4) writing skills.These language skills are the basic of language uses. As a whole, the difficulties faced by students vary, such as intelligence physical and psychologist factors; intelligence, talent, interest, motivation, and ways of learning) and non-intelligence factors. There are internal and external factors as well (family, school, society factors). This study is to know; (1) what the most difficult language skills students understand, (2) the reasons of students at the difficulties in the language skills, and (3) how the students face their difficulties. The method of this study is descriptive, conducted in ILFS class of English Program and Translation Program at Samarkand State Institute of Foreign Languages, Uzbekistan. The numbers of students are 35 (9 males and 26 females). The time of this study was semester II in 2019, and data was taken in March 2019. Technic of collecting data is using test and interview as well as the evaluation sheet in semester I as the diagnostic data of studentsâ€™ difficulties toward 4 language skills. Data analysis consists of qualitative and quantitative. The lowest average mark is of listening (61.68), speaking (69.07), writing (71.89), and reading (76.29).From the questionnairesâ€™ sheet given to the students, it can be concluded that; students like Indonesian language (85.71%), the pronunciation of Indonesian language is different to source language (65.71%), symbols/letters writing in Indonesian language is not different (80.00%), there is no difficulty in uttering Indonesian language words (77.14%), guidance book used in learning process is good and helpful Indonesia (91.43%), in listening, speaker speaks very fast (97.14%), difficulties in listening (94.29%), there is no difficulty in readingskills (85.71%), there is no difficulty in writing skills (80.00%), there is difficulty in speaking skills (71.43%), the most liked language skills in learning is reading (57.14%), the most hated language skills in learning is listening (94.29%), the most difficult language skills in learning is listening (88.57%), the easiest language skills in learning is reading (71.43%),and the studentsâ€™ action facing the difficulties in learning Indonesian language is asking the teacher (85.71%). It is expected that the ILFS teaching concerns on studentsâ€™ difficulties firstly and give motivation during the teaching process in order that the students are motivated to learn Indonesian language.